(untitled) - Prof. Dr. Petter Asp (Universität Stockholm); Prof. Dr. Luigi Foffani (Universität Modena und Reggio Emilia); Prof. Dr. Maria Kaiafa-Gbandi (Aristoteles Universität Thessaloniki); Prof. Dr. Helmut Satzger (Ludwig-Maximilians-Universität München); Prof. Dr. Ingeborg Zerbes (Universität Bremen) (EuCLR European Criminal Law Review, 2012)
The European Criminal Law Review (EuCLR) is a journal dedicated to the development of European Criminal Law and the cooperation in criminal matters within the European Union. In these areas the Lisbon Treaty has supposedly brought about the most important changes and also the greatest challenges for the future.It is the journal’s ambition to provide a primary forum for comprehensive discussion and critical analysis of all questions arising in relation to European Criminal Law. It will include articles and relevant material on topics such as- the harmonisation of national criminal law in consideration of European legal instruments,- the implementation of the principle of mutual recognition in the area of cooperation in criminal matters and the development towards the creation of a European Public Prosecutor,- the emergence of a balanced European Criminal Policy based on fundamental rights, freedom and democracy with particular reference to the Charter of Fundamental Rights of the European Union and the European Convention on Human Rights.